2013
DOI: 10.1590/s0104-07072013000100023
|View full text |Cite
|
Sign up to set email alerts
|

Nurse training in Japan: contribution to the foundation of the Casa de Parto birthing center in Rio de Janeiro

Abstract: This study was performed using a historical-social approach and aimed at discussing how the Brazilian nurse midwives trained in the Japanese birthing centers helped implement Casa de Parto in Rio de Janeiro-RJ in 2003. The primary sources of information were written and oral documentation found in collections and semi-structured interviews. The analysis happened in three steps: organization, classification and data triangulation. In order to support the analysis, concepts of habitus, field, symbolic capital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…Study authors reported that the concept of cost effectiveness associated with MUs was not always clear to commissioners, managers and professionals (14,17,18). The concept of MU being "cost-saving" was often mentioned together with the status of nancial constraint and the urgent need for healthcare organisations to save money (14,(17)(18)(19)(21)(22)(23)(24)(25):…”
Section: Cost and Nancing Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study authors reported that the concept of cost effectiveness associated with MUs was not always clear to commissioners, managers and professionals (14,17,18). The concept of MU being "cost-saving" was often mentioned together with the status of nancial constraint and the urgent need for healthcare organisations to save money (14,(17)(18)(19)(21)(22)(23)(24)(25):…”
Section: Cost and Nancing Systemsmentioning
confidence: 99%
“…Similarly, in Canada and Brazil, the new national guideline promoting the MU model of care was reported as a key trigger for an implementation process towards MUs (22,24,26).…”
Section: National Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations